The Impact of Food Energy Consumption and Poverty Levels on the Prevalence of Food Inadequacy in Indonesia - Afini, Nur; Prayitno, Andaru Rachmaning Dias (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2025)
Food security in Indonesia continues to face serious challenges despite the declining poverty rate, indicating that income growth alone does not necessarily translate into improved nutritional outcomes. This study examines the effects of household food energy consumption and poverty levels on the prevalence of inadequate food consumption across 34 provinces in Indonesia from 2019 - 2024. The findings reveal that higher household food energy consumption significantly reduces the prevalence of inadequate food consumption, whereas poverty levels do not exhibit a significant effect. These results diverge from much of the existing literature that positions poverty as the primary determinant of food insecurity. The novelty of this study lies in demonstrating that food energy adequacy exerts a more direct and consistent influence than poverty status in explaining food insecurity at the provincial level. The policy implication is that poverty alleviation alone is insufficient to address nutritional deficiencies. Instead, interventions should focus on improving household access to energy-dense and nutritious foods through local agricultural development, food price stabilization, and targeted nutrition programs. Such strategies are considered more effective in supporting the achievement of the Zero Hunger target in Indonesia.